Entropy Analysis of a Variable Viscosity MHD Couette Flow Between Two Concentric Pipes with Convective Cooling - MAKINDE, Oluwole Daniel; EEGUNJOBI, Adetayo Samuel (Engineering Transactions, 2020)
This paper addresses the combined effects of the magnetic field, thermal buoyancy force, viscous dissipation, Joule heating and temperature-dependent viscosity on the Couette flow of an incompressible conducting fluid between two concentric vertical pipes. It is assumed that convective cooling occurs at the surface of the outer moving pipe while the surface of the inner fixed pipe is maintained at a constant temperature. The nonlinear equations for momentum and energy are obtained and solved numerically using a shooting method coupled with the Runge-Kutta-Fehlberg integration procedure. Relevant results depicting the effects of embedded thermophysical parameters on the velocity and temperature profiles, skin friction, the Nusselt number, entropy generation rate and the Bejan number are presented graphically and discussed. It is found that an increase in the magnetic field intensity boosts the entropy generation rate while an increase in convective cooling lessens it.